Plasma Selenium Concentration and Glutathione Peroxidase Activity in Red Blood Cells of Laying Hens Fed Sodium Selenite or Zinc-L-Selenomethionine - Chantiratikul, A.; Aengwanich, W.; Chinrasri, O.; Chantiratikul, P. (International Journal of Poultry Science, 2008)
The objective of this study was to determine the effect of sodium selenite and zinc-L-selenomethionine on plasma selenium (Se) concentration and glutathione peroxidase (GSH-Px) activity in the red blood cells (RBC) of laying hens. Two hundred twenty four CP Browns aged 71 weeks were divided according to a 2x3 factorial in completely randomized design. One more group without additional Se supplementation was used as negative control. Each treatment consisted of four replicates and each replicate contained eight hens. The dietary treatments were T1: basal diet, T2, T3 and T4: basal diets added 0.3, 1.0 and 3.0 mg Se from sodium selenite/kg, respectively, T5, T6 and T7: basal diets added 0.3, 1.0 and 3.0 mg Se from zinc-L-selenomethionine/kg, respectively. The findings revealed that the plasma Se concentration of hens received supplemented zinc-L-selenomethionine diets was higher (p